Managing organizational decision making - Miller, Susan (Henry Stewart Talks, 2010)
What is a decision?, Types of decision, Ways of making decisions, Rationality in decision-making, Incrementalism: a step by step approach, The intriguing world of the 'garbage can', Power and 'non decisions', Explaining why decision processes differ, Getting decisions implemented successfully